Low-temperature electrolyte and lithium battery
By using a specific combination of low-temperature electrolytes, including linear carboxylate and linear carbonate, the problem of degradation of lithium batteries in low-temperature environments is solved, the circulation performance and safety performance are improved, and the applicable temperature range is expanded.
Patent Information
- Application Number
- CN202411451949.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium batteries have degraded performance in low temperature environments, especially their capacity and magnification are affected, which may lead to safety accidents.
A low-temperature electrolyte is used, including linear carboxylic acid ester and linear carbonate as organic solvents, combined with specific lithium salts and additives, to improve the low-temperature performance of the electrolyte.
It effectively reduces the low-temperature internal resistance of lithium batteries, improves circulation and safety performance, and expands the applicable temperature range of lithium batteries.
Smart Images

Figure CN119170877A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a low-temperature electrolyte and a lithium battery. Background Art
[0002] Lithium batteries have the advantages of high energy density, lightness, fast charging and no memory effect, and have been widely used in mobile phones, laptops, electric vehicles, energy storage systems and other fields. However, the performance of lithium batteries is greatly affected by the ambient temperature. The applicable temperature of general lithium batteries is -20 to 55℃. The capacity and rate of lithium batteries will be affected in an environment of -20℃. If the temperature is further reduced, lithium deposition may occur, leading to safety accidents.
[0003] Therefore, how to reduce the low-temperature internal resistance of lithium batteries and improve the cycle performance and safety performance of lithium batteries is one of the development directions in this field. Summary of the invention
[0004] The present application aims to provide a low-temperature electrolyte and a lithium battery to alleviate the problem of performance degradation of the lithium battery at low temperatures and to expand the applicable temperature range of the lithium battery.
[0005] The embodiment of the present application is implemented as follows:
[0006] In a first aspect, the present invention provides a low-temperature electrolyte, including an organic solvent, a lithium salt and an additive, wherein the organic solvent includes a linear carboxylate and a linear carbonate, and the linear carboxylate has a general structural formula of The R1 is a chloroalkane or a bromoalkane with a carbon number of ≤4, and the R2 is a chloroalkane or a bromoalkane with a carbon number of ≤2.
[0007] In one embodiment of the present application, in said R1 and said R2: the number of chlorine atoms substituted is ≤4, and / or the number of bromine atoms substituted is ≤4.
[0008] In one embodiment of the present application, the linear carbonate has the general structural formula: The R3 and R4 are respectively alkanes or chlorinated or brominated alkanes with carbon number ≤ 4.
[0009] In one embodiment of the present application, in said R3 and said R4: the number of chlorine atoms substituted is ≤6, and / or the number of bromine atoms substituted is ≤6.
[0010] In one embodiment of the present application, the mass percentage of the linear carboxylic acid ester in the low-temperature electrolyte is 5-50%; and / or
[0011] The mass proportion of the linear carbonate in the low-temperature electrolyte is 10-50%.
[0012] In one embodiment of the present application, the organic solvent further includes a component A, and the component A includes at least one of a cyclic carbonate, a cyclic carboxylic acid ester, an ether solvent, a nitrile solvent, and a sulfone solvent.
[0013] In one embodiment of the present application, the mass proportion of the component A in the low-temperature electrolyte is 5-40%.
[0014] In one embodiment of the present application, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethylsulfonate, lithium tetrafluoroborate, lithium nitrate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium carbonate, and lithium perchlorate; and / or
[0015] The mass percentage of the lithium salt in the low-temperature electrolyte is 5-30%; and / or
[0016] The additive comprises at least one of vinylene carbonate, vinyl vinylene carbonate, vinyl sulfite, propylene sulfite, butylene sulfite, ethylene sulfite, propane sultone, propylene sultone, butylene sultone, fluoroethylene carbonate, and difluoroethylene carbonate; and / or
[0017] The additive accounts for 0.1-10% by mass in the low-temperature electrolyte.
[0018] In a second aspect, an embodiment of the present application provides a lithium battery, comprising a positive electrode, a negative electrode, a separator, and the low-temperature electrolyte described in any one of the first aspects.
[0019] In one embodiment of the present application, the positive electrode includes a positive electrode current collector and a positive electrode active material, the positive electrode active material is arranged on the surface of the positive electrode current collector, and the positive electrode active material includes at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based layered oxide, and lithium nickel manganese oxide; and / or
[0020] The negative electrode material used in the negative electrode includes at least one of spinel lithium titanate, high-phase pyrolytic graphite, artificial graphite, natural graphite, graphitized carbon fiber, graphitized mesophase carbon microspheres, hard carbon, soft carbon, carbon nanotubes, graphene, graphene composite materials, silicon materials, silicon oxide, silicon-carbon composite materials, metal copper and its alloys, metal lithium and its alloys, lithium-carbon composite materials, tin-based materials, and tin oxide materials; and / or
[0021] The surface capacity of the positive electrode is 0.5-5 mAh / cm 2 ; and / or
[0022] The surface capacity of the negative electrode is 0.5-5 mAh / cm 2 ; and / or
[0023] The porosity of the separator is ≥40%.
[0024] The technical solution provided in the present application reduces the low-temperature internal resistance of lithium-ion batteries and improves the cycle performance, safety performance and power performance of lithium-ion batteries in low-temperature environments by combining specific fluoroalkane or bromoalkane linear carboxylates with specific fluoroalkane or bromoalkane linear carbonates. DETAILED DESCRIPTION
[0025] The following will be clearly and completely described in conjunction with the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0027] In this application, unless otherwise indicated, the term "including" means "including but not limited to." The terms first, second, third, etc. are used merely as labels and do not impose a numerical requirement or establish a sequence.
[0028] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0029] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0030] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0031] In a first aspect, the present invention provides a low-temperature electrolyte, including an organic solvent, a lithium salt and an additive, wherein the organic solvent includes a linear carboxylate and a linear carbonate, and the linear carboxylate has a general structural formula of R1 is a chloroalkane or a bromoalkane having 4 or less carbon atoms, and R2 is a chloroalkane or a bromoalkane having 2 or less carbon atoms.
[0032] In some embodiments, the number of chlorine atoms substituted in R1 and R2 is ≤4.
[0033] In some embodiments, the number of bromine atoms substituted in R1 and R2 is ≤4.
[0034] In some embodiments, the linear carbonate has the general formula R3 and R4 are alkane or chlorinated or brominated alkane having carbon number ≤ 4.
[0035] In some embodiments, the number of chlorine atoms substituted in R3 and R4 is ≤6.
[0036] In some embodiments, the number of bromine atoms substituted in R3 and R4 is ≤6.
[0037] Illustratively, the selected linear carboxylic acid ester includes at least one of methyl chloroacetate, ethyl chloroformate, ethyl chloroformate, methyl chloroacetate, methyl bromoacetate, ethyl bromoformate, ethyl bromoformate, and methyl bromoacetate.
[0038] Exemplarily, the selected linear carbonate includes at least one of ethyl methyl chlorocarbonate, methyl propyl chlorocarbonate, chloromethyl trifluoroethyl carbonate, bis(2,2,2-trifluoroethyl)chlorocarbonate, ethyl methyl bromocarbonate, methyl propyl bromocarbonate, bromomethyl trifluoroethyl carbonate, and bis(2,2,2-trifluoroethyl)bromocarbonate.
[0039] In some embodiments, the mass proportion of the linear carboxylic acid ester in the low-temperature electrolyte is 5-50%. For example, the mass proportion of the linear carboxylic acid ester in the low-temperature electrolyte is 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 22%, 24%, 25%, 26%, 28%, 29%, 30%, 31%, 33%, 35%, 37%, 39%, 40%, 42%, 45%, 47%, 48% or 50%, etc.
[0040] In some embodiments, the mass proportion of the linear carbonate in the low-temperature electrolyte is 10-50%. For example, the mass proportion of the linear carbonate in the low-temperature electrolyte is 10%, 12%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 22%, 24%, 25%, 26%, 28%, 29%, 30%, 31%, 33%, 35%, 37%, 39%, 40%, 42%, 45%, 47%, 48% or 50%, etc.
[0041] In some embodiments, the organic solvent further includes component A, and component A includes at least one of cyclic carbonate, cyclic carboxylic acid ester, ether solvent, nitrile solvent, and sulfone solvent.
[0042] In some embodiments, the mass proportion of component A in the low-temperature electrolyte is 5-40%. For example, the mass proportion of component A in the low-temperature electrolyte is 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 22%, 24%, 25%, 26%, 28%, 29%, 30%, 31%, 33%, 35%, 37%, 39% or 40%, etc.
[0043] In some embodiments, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethylsulfonate, lithium tetrafluoroborate, lithium nitrate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium carbonate, and lithium perchlorate.
[0044] In some embodiments, the mass proportion of lithium salt in the low-temperature electrolyte is 5-30%. For example, the mass proportion of lithium salt in the low-temperature electrolyte is 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 22%, 24%, 25%, 26%, 28%, 29% or 30%.
[0045] In some embodiments, the additive includes at least one of vinylene carbonate, vinyl vinylene carbonate, vinyl sulfite, propylene sulfite, butylene sulfite, ethylene sulfite, propane sultone, propylene sultone, butylene sultone, fluoroethylene carbonate, and difluoroethylene carbonate.
[0046] In some embodiments, the mass proportion of the additive in the low-temperature electrolyte is 0.1-10%. For example, the mass proportion of the additive in the low-temperature electrolyte is 0.1%, 0.3%, 0.5%, 0.6%, 0.8%, 1.0%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2.0%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 2.9%, 3.0%, 3.2%, 3.5%, 3.7%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 5.1%, 5.2%, 5.3%, 5.9%, 5.1%, 5. .4%, 4.5%, 4.7%, 4.9%, 5.0%, 5.2%, 5.5%, 5.6%, 5.8%, 6.0%, 6.1%, 6.3%, 6.5%, 6.8%, 6.9%, 7.0%, 7.2%, 7.5%, 7.8%, 8.0%, 8.3%, 8.5%, 8.8%, 9.0%, 9.2%, 9.5%, 9.6%, 9.8% or 10%, etc.
[0047] In a second aspect, an embodiment of the present application provides a lithium battery, comprising a positive electrode, a negative electrode, a separator, and the low-temperature electrolyte of any one of the first aspects.
[0048] In some embodiments, the positive electrode includes a positive electrode collector and a positive electrode active material, the positive electrode active material is arranged on the surface of the positive electrode collector, and the positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based layered oxide, and lithium nickel manganese oxide.
[0049] In some embodiments, the negative electrode material used for the negative electrode includes at least one of spinel lithium titanate, high-phase pyrolytic graphite, artificial graphite, natural graphite, graphitized carbon fiber, graphitized mesophase carbon microspheres, hard carbon, soft carbon, carbon nanotubes, graphene, graphene composites, silicon materials, silicon oxide, silicon-carbon composites, metallic copper and its alloys, metallic lithium and its alloys, lithium-carbon composites, tin-based materials, and tin oxide materials.
[0050] In some embodiments, the surface capacity of the positive electrode is 0.5-5 mAh / cm 2 For example, the positive electrode surface capacity is 0.5 mAh / cm 2 、0.7mAh / cm 2 、0.8mAh / cm 2 、0.9mAh / cm 2 、1.0mAh / cm2 、1.2mAh / cm 2 、1.3mAh / cm 2 、1.5mAh / cm 2 、1.7mAh / cm 2 、1.8mAh / cm 2 、2.0mAh / cm 2 、2.2mAh / cm 2 、2.4mAh / cm 2 、2.5mAh / cm 2 、2.7mAh / cm 2 、2.8mAh / cm 2 、3.0mAh / cm 2 、3.1mAh / cm 2 、3.3mAh / cm 2 、3.5mAh / cm 2 、3.7mAh / cm 2 、3.9mAh / cm 2 、4.0mAh / cm 2 、4.2mAh / cm 2 、4.4mAh / cm 2 、4.6mAh / cm 2 、4.8mAh / cm 2 or 5.0mAh / cm 2 wait.
[0051] In some embodiments, the surface capacity of the negative electrode is 0.5-5 mAh / cm 2 For example, the negative electrode surface capacity is 0.5 mAh / cm 2 、0.7mAh / cm 2 、0.8mAh / cm 2 、0.9mAh / cm 2 、1.0mAh / cm 2 、1.2mAh / cm 2 、1.3mAh / cm 2 、1.5mAh / cm 2 、1.7mAh / cm 2 、1.8mAh / cm 2 、2.0mAh / cm 2 、2.2mAh / cm 2 、2.4mAh / cm 2 、2.5mAh / cm 2 、2.7mAh / cm 2 、2.8mAh / cm 2 、3.0mAh / cm2 、3.1mAh / cm 2 、3.3mAh / cm 2 、3.5mAh / cm 2 、3.7mAh / cm 2 、3.9mAh / cm 2 、4.0mAh / cm 2 、4.2mAh / cm 2 、4.4mAh / cm 2 、4.6mAh / cm 2 、4.8mAh / cm 2 or 5.0mAh / cm 2 wait.
[0052] In some embodiments, the porosity of the diaphragm is ≥ 40%. For example, the porosity of the diaphragm is set to 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58% or 59%, etc.
[0053] The present application reduces the low-temperature internal resistance and improves the conduction dynamics of the lithium battery by setting an electrolyte suitable for low temperatures in the lithium battery, and further improves the low-temperature internal resistance and conduction dynamics by coordinating the surface capacity design of the positive and negative electrodes and the diaphragm design, and ensures the infiltration efficiency of the electrolyte, thereby further promoting the low-temperature performance of the battery.
[0054] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0055] Example 1
[0056] After 12 g of ethyl bromobutyrate, 5 g of ethyl chloroacetate, 24 g of ethyl methyl chlorocarbonate, and 1 g of vinylene carbonate are mixed evenly, 8 g of anhydrous lithium hexafluorophosphate is weighed and added and stirred sufficiently to completely dissolve it into a colorless transparent liquid to obtain a low-temperature electrolyte.
[0057] Nickel cobalt manganese oxide and silicon carbon composite materials are used as the positive and negative active materials of the battery respectively. The surface capacity of the positive electrode is 2mAh / cm 2 The surface capacity of the negative electrode is 2.2 mAh / cm 2 , select a diaphragm with a porosity of 45%, make a laminated soft-pack battery with a capacity of 5Ah, and inject low-temperature electrolyte.
[0058] Example 2
[0059] After 8 g of ethyl bromobutyrate, 7 g of ethyl chloroacetate, 24 g of ethyl methyl chlorocarbonate, and 1 g of vinylene carbonate are mixed evenly, 8 g of anhydrous lithium hexafluorophosphate is weighed and added and stirred sufficiently to completely dissolve it into a colorless transparent liquid to obtain a low-temperature electrolyte.
[0060] Nickel cobalt manganese oxide and silicon carbon composite materials are used as the positive and negative active materials of the battery respectively. The surface capacity of the positive electrode is 2mAh / cm 2 The surface capacity of the negative electrode is 2.2 mAh / cm 2 , select a diaphragm with a porosity of 45%, make a laminated soft-pack battery with a capacity of 5Ah, and inject low-temperature electrolyte.
[0061] Example 3
[0062] After mixing 12 g of ethyl bromobutyrate, 5 g of ethyl chloroacetate, 15 g of ethyl methyl chlorocarbonate, and 1 g of vinylene carbonate evenly, 8 g of anhydrous lithium hexafluorophosphate was weighed and added and stirred sufficiently to completely dissolve it into a colorless transparent liquid to obtain a low-temperature electrolyte.
[0063] Nickel cobalt manganese oxide and silicon carbon composite materials are used as the positive and negative active materials of the battery respectively. The surface capacity of the positive electrode is 2mAh / cm 2 The surface capacity of the negative electrode is 2.2 mAh / cm 2 , select a diaphragm with a porosity of 45%, make a laminated soft-pack battery with a capacity of 5Ah, and inject low-temperature electrolyte.
[0064] Example 4
[0065] After 12 g of ethyl bromobutyrate, 5 g of ethyl chloroacetate, 8 g of ethyl methyl chlorocarbonate, and 1 g of vinylene carbonate are mixed evenly, 8 g of anhydrous lithium hexafluorophosphate is weighed and added and stirred sufficiently to completely dissolve it into a colorless transparent liquid to obtain a low-temperature electrolyte.
[0066] Nickel cobalt manganese oxide and silicon carbon composite materials are used as the positive and negative active materials of the battery respectively. The surface capacity of the positive electrode is 2mAh / cm 2 The surface capacity of the negative electrode is 2.2 mAh / cm 2 , select a diaphragm with a porosity of 45%, make a laminated soft-pack battery with a capacity of 5Ah, and inject low-temperature electrolyte.
[0067] Example 5
[0068] After 17 g of methyl chloroacetate, 24 g of ethyl methyl chlorocarbonate and 1 g of vinylene carbonate are mixed evenly, 8 g of anhydrous lithium hexafluorophosphate is weighed and added and stirred sufficiently to completely dissolve it into a colorless transparent liquid to obtain a low-temperature electrolyte.
[0069] Nickel cobalt manganese oxide and silicon carbon composite materials are used as the positive and negative active materials of the battery respectively. The surface capacity of the positive electrode is 2mAh / cm 2 The surface capacity of the negative electrode is 2.2 mAh / cm 2 , select a diaphragm with a porosity of 45%, make a laminated soft-pack battery with a capacity of 5Ah, and inject low-temperature electrolyte.
[0070] Example 6
[0071] After 12 g of ethyl bromobutyrate, 5 g of ethyl chloroacetate, 24 g of bis(2,2,2-trifluoroethyl)bromocarbonate, and 1 g of vinylene carbonate are mixed evenly, 8 g of anhydrous lithium hexafluorophosphate is weighed and added and stirred sufficiently to completely dissolve it into a colorless transparent liquid to obtain a low-temperature electrolyte.
[0072] Nickel cobalt manganese oxide and silicon carbon composite materials are used as the positive and negative active materials of the battery respectively. The surface capacity of the positive electrode is 2mAh / cm 2 The surface capacity of the negative electrode is 2.2 mAh / cm 2 , select a diaphragm with a porosity of 45%, make a laminated soft-pack battery with a capacity of 5Ah, and inject low-temperature electrolyte.
[0073] Example 7
[0074] After 12 g of ethyl bromobutyrate, 5 g of ethyl chloroacetate, 24 g of ethyl methyl chlorocarbonate, and 0.1 g of vinylene carbonate are mixed evenly, 8 g of anhydrous lithium hexafluorophosphate is weighed and added and stirred sufficiently to completely dissolve it into a colorless transparent liquid to obtain a low-temperature electrolyte.
[0075] Nickel cobalt manganese oxide and silicon carbon composite materials are used as the positive and negative active materials of the battery respectively. The surface capacity of the positive electrode is 2mAh / cm 2 The surface capacity of the negative electrode is 2.2 mAh / cm 2 , select a diaphragm with a porosity of 45%, make a laminated soft-pack battery with a capacity of 5Ah, and inject low-temperature electrolyte.
[0076] Example 8
[0077] After 12 g of ethyl bromobutyrate, 5 g of ethyl chloroacetate, 24 g of ethyl methyl chlorocarbonate, and 5.4 g of vinylene carbonate are mixed evenly, 8 g of anhydrous lithium hexafluorophosphate is weighed and added and stirred sufficiently to completely dissolve it into a colorless transparent liquid to obtain a low-temperature electrolyte.
[0078] Nickel cobalt manganese oxide and silicon carbon composite materials are used as the positive and negative active materials of the battery respectively. The surface capacity of the positive electrode is 2mAh / cm 2 The surface capacity of the negative electrode is 2.2 mAh / cm 2, select a diaphragm with a porosity of 45%, make a laminated soft-pack battery with a capacity of 5Ah, and inject low-temperature electrolyte.
[0079] Example 9
[0080] After 12 g of ethyl bromobutyrate, 5 g of ethyl chloroacetate, 24 g of ethyl methyl chlorocarbonate, and 1 g of propylene sultone are mixed evenly, 8 g of anhydrous lithium hexafluorophosphate is weighed and added and stirred sufficiently to completely dissolve it into a colorless transparent liquid to obtain a low-temperature electrolyte.
[0081] Nickel cobalt manganese oxide and silicon carbon composite materials are used as the positive and negative active materials of the battery respectively. The surface capacity of the positive electrode is 2mAh / cm 2 The surface capacity of the negative electrode is 2.2 mAh / cm 2 , select a diaphragm with a porosity of 45%, make a laminated soft-pack battery with a capacity of 5Ah, and inject low-temperature electrolyte.
[0082] Example 10
[0083] 12 g of ethyl bromobutyrate, 5 g of ethyl chloroacetate, 24 g of ethyl methyl chlorocarbonate, 1 g of vinylene carbonate, 8 g of trifluoropropylene carbonate (TFPC), 22 g of γ-butyrolactone (GBL), and 3 g of dimethyl sulfoxide were mixed evenly, and then 8 g of anhydrous lithium hexafluorophosphate was weighed and added and stirred sufficiently to completely dissolve it into a colorless transparent liquid to obtain a low-temperature electrolyte.
[0084] Nickel cobalt manganese oxide and silicon carbon composite materials are used as the positive and negative active materials of the battery respectively. The surface capacity of the positive electrode is 2mAh / cm 2 The surface capacity of the negative electrode is 2.2 mAh / cm 2 , select a diaphragm with a porosity of 45%, make a laminated soft-pack battery with a capacity of 5Ah, and inject low-temperature electrolyte.
[0085] Comparative Example 1
[0086] After 12 g of ethyl butyrate, 5 g of ethyl acetate, 24 g of ethyl methyl carbonate and 1 g of vinylene carbonate are mixed evenly, 8 g of anhydrous lithium hexafluorophosphate is weighed and added and stirred sufficiently to completely dissolve it into a colorless transparent liquid to obtain a low-temperature electrolyte.
[0087] Nickel cobalt manganese oxide and silicon carbon composite materials are used as the positive and negative active materials of the battery respectively. The surface capacity of the positive electrode is 2mAh / cm 2 The surface capacity of the negative electrode is 2.2 mAh / cm 2 , select a diaphragm with a porosity of 45%, make a laminated soft-pack battery with a capacity of 5Ah, and inject low-temperature electrolyte.
[0088] Comparative Example 2
[0089] After mixing 27 g of dimethyl carbonate, 18 g of ethylene carbonate, 18 g of methyl acetate, 18 g of γ-butyrolactone and 1 g of vinylene carbonate evenly, 8 g of anhydrous lithium hexafluorophosphate was weighed and added and stirred sufficiently to completely dissolve it into a colorless transparent liquid to obtain a low-temperature electrolyte.
[0090] Nickel cobalt manganese oxide and silicon carbon composite materials are used as the positive and negative active materials of the battery respectively. The surface capacity of the positive electrode is 2mAh / cm 2 The surface capacity of the negative electrode is 2.2 mAh / cm 2 , select a diaphragm with a porosity of 45%, make a laminated soft-pack battery with a capacity of 5Ah, and inject low-temperature electrolyte.
[0091] In the soft-pack lithium batteries of Examples 1-10 and Comparative Examples 1-2, the amount of low-temperature electrolyte injected into each lithium battery was 12 g. After the low-temperature electrolyte was injected and left to stand for 24 hours, the electrolyte was charged at 0.1 C (0.5 mA / cm 2 ) After the battery is converted into capacity at room temperature using a small current, the performance of the battery is tested.
[0092] Test Item 1: Battery Capacity Retention at -20°C. The soft pack battery was heated at 0.2C (1mA / cm 2 ) rate current density to 4.3V, and after standing in a low-temperature box at -20 degrees Celsius for 12 hours, the soft-pack battery was discharged to 2.5V at a current density of 0.2C rate, and the discharge capacity of the soft-pack batteries corresponding to different electrolytes was compared.
[0093] Test item 2: Battery internal resistance at -20 degrees. After the soft-pack battery is placed in a low-temperature box at -20 degrees for 12 hours, the internal resistance of the soft-pack battery is tested with a battery internal resistance tester to compare the internal resistance of soft-pack batteries with different electrolytes.
[0094] Test item 3: Battery cycle performance at -20 degrees. The soft pack battery was placed in a low temperature box at -20 degrees for 12 hours and then subjected to low temperature cycle test: first, 0.2C (1mA / cm 2 ) rate current density to 4.3V and then 0.2C (1mA / cm 2 ) rate to 2.5 V, and charge and discharge cycles were carried out according to the above steps to compare the capacity retention rates of different electrolyte systems after 50 cycles.
[0095] The test results are shown in Table 1.
[0096] Table 1
[0097]
[0098]
[0099] From this we can see that:
[0100] Comparing Examples 1-10 with Comparative Examples 1-2, the internal resistance of Examples 1-10 under low temperature conditions is basically maintained at a relatively low state, and it is not easy to have too fast performance degradation caused by excessive internal resistance. Moreover, after 50 cycles at low temperature, the low-temperature cycle capacity retention rate is relatively high, indicating that the technical solution provided in the present application can effectively improve the cycle performance and safety performance of lithium batteries at low temperatures, and alleviate the problem of performance degradation of lithium batteries at low temperatures.
[0101] By comparing Example 1 with Example 2, Example 3, and Example 4, it can be seen that adjusting the amount of linear carboxylate or linear carbonate within a certain range and changing the mass ratio of linear carboxylate to linear carbonate can still achieve good results, and within the set range provided in the present application, the higher the mass ratio of linear carboxylate to linear carbonate, the smaller the internal resistance, and the smaller the mass ratio of linear carboxylate to linear carbonate, the higher the low-temperature cycle capacity retention rate.
[0102] Comparing Example 1 with Example 5 and Example 6, it can be seen that replacing the selection of linear carboxylic acid ester and linear carbonate within the limited conditions of this application can still achieve a good improvement effect. Comparing Example 1 with Example 7, Example 8, and Example 9, it is shown that adding an appropriate proportion of additives to the electrolyte system within the limited conditions of this application can have a certain improvement effect on low-temperature internal resistance or low-temperature cycle performance, while other properties are still maintained at a good level.
[0103] Comparing Example 1 with Example 10, it is shown that in the electrolyte system provided in the present application, even if other solvents are added within a certain range, such as cyclic carbonates, cyclic carboxylic acid ester solvents, sulfone solvents, etc., the cycle performance of the lithium battery at low temperature is still well improved, while the safety is maintained at a good level.
[0104] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A low-temperature electrolyte, characterized in that: It comprises an organic solvent, a lithium salt and an additive, wherein the organic solvent comprises a linear carboxylate and a linear carbonate, and the linear carboxylate has a general structural formula of The R1 is a chloroalkane or a bromoalkane with a carbon number of ≤4, and the R2 is a chloroalkane or a bromoalkane with a carbon number of ≤2.
2. The low-temperature electrolyte according to claim 1, characterized in that In the R1 and the R2: the number of chlorine atoms substituted is ≤4, and / or the number of bromine atoms substituted is ≤4.
3. The low-temperature electrolyte according to claim 1, characterized in that The general structural formula of the linear carbonate is The R3 and R4 are respectively alkanes or chlorinated or brominated alkanes with carbon number ≤ 4.
4. The low-temperature electrolyte according to claim 3, characterized in that In the R3 and the R4: the number of chlorine atoms substituted is ≤6, and / or the number of bromine atoms substituted is ≤6.
5. The low-temperature electrolyte according to claim 1, characterized in that: The mass percentage of the linear carboxylic acid ester in the low-temperature electrolyte is 5-50%; and / or The mass proportion of the linear carbonate in the low-temperature electrolyte is 10-50%.
6. The low-temperature electrolyte according to claim 1, characterized in that The organic solvent further includes component A, and the component A includes at least one of cyclic carbonate, cyclic carboxylic acid ester, ether solvent, nitrile solvent, and sulfone solvent.
7. The low-temperature electrolyte according to claim 6, characterized in that: The mass proportion of the component A in the low-temperature electrolyte is 5-40%.
8. The low-temperature electrolyte according to claim 1, characterized in that The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethylsulfonate, lithium tetrafluoroborate, lithium nitrate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium carbonate, and lithium perchlorate; and / or The mass percentage of the lithium salt in the low-temperature electrolyte is 5-30%; and / or The additive comprises at least one of vinylene carbonate, vinyl vinylene carbonate, vinyl sulfite, propylene sulfite, butylene sulfite, ethylene sulfite, propane sultone, propylene sultone, butylene sultone, fluoroethylene carbonate, and difluoroethylene carbonate; and / or The additive accounts for 0.1-10% by mass in the low-temperature electrolyte.
9. A lithium battery, characterized in that: It comprises a positive electrode, a negative electrode, a separator, and the low-temperature electrolyte according to any one of claims 1 to 8.
10. The lithium battery according to claim 9, characterized in that: The positive electrode comprises a positive electrode current collector and a positive electrode active material, wherein the positive electrode active material is arranged on the surface of the positive electrode current collector, and the positive electrode active material comprises at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based layered oxide, and lithium nickel manganese oxide; and / or The negative electrode material used in the negative electrode includes at least one of spinel lithium titanate, high-phase pyrolytic graphite, artificial graphite, natural graphite, graphitized carbon fiber, graphitized mesophase carbon microspheres, hard carbon, soft carbon, carbon nanotubes, graphene, graphene composite materials, silicon materials, silicon oxide, silicon-carbon composite materials, metal copper and its alloys, metal lithium and its alloys, lithium-carbon composite materials, tin-based materials, and tin oxide materials; and / or The surface capacity of the positive electrode is 0.5-5 mAh / cm 2 ; and / or The surface capacity of the negative electrode is 0.5-5 mAh / cm 2 ; and / or The porosity of the separator is ≥40%.
Citation Information
Patent Citations
Lithium ion battery electrolyte solution and lithium ion battery thereof
CN107681198A
Rate type lithium ion battery electrolytic solution with high and low temperature performance and lithium ion battery
CN113471535A
Secondary battery and method for manufacturing the same
CN116435620A
